2021
DOI: 10.1093/mnras/stab2039
|View full text |Cite
|
Sign up to set email alerts
|

White dwarf–main-sequence binaries from Gaia EDR3: the unresolved 100 pc volume-limited sample

Abstract: We use the data provided by the Gaia Early Data Release 3 to search for a highly-complete volume-limited sample of unresolved binaries consisting of a white dwarf and a main sequence companion (i.e. WDMS binaries) within 100 pc. We select 112 objects based on their location within the Hertzsprung-Russell diagram, of which 97 are new identifications. We fit their spectral energy distributions (SED) with a two-body fitting algorithm implemented in VOSA (Virtual Observatory SED Analyser) to derive the effective t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 117 publications
3
22
0
Order By: Relevance
“…5 as open symbols those objects with presumably helium-cores, founding 119 WDMS and 35 DWD of these systems, which represent 15% and 17% of its respective sub-population. These percentages are in agreement with other studies of the Gaia white dwarf population -see, for instance, (Rebassa-Mansergas et al 2021), where 46 low-mass objects have been found out of 235 WDMS (19%).…”
Section: The Fraction Of Helium-core White Dwarfssupporting
confidence: 93%
See 2 more Smart Citations
“…5 as open symbols those objects with presumably helium-cores, founding 119 WDMS and 35 DWD of these systems, which represent 15% and 17% of its respective sub-population. These percentages are in agreement with other studies of the Gaia white dwarf population -see, for instance, (Rebassa-Mansergas et al 2021), where 46 low-mass objects have been found out of 235 WDMS (19%).…”
Section: The Fraction Of Helium-core White Dwarfssupporting
confidence: 93%
“…Note that this classification did not pretend to be exhaustive and rigorous, but just a rough classification. Note also that the sources classified as unresolved binaries are very likely to belong to the WDMS or cataclysmic variable types since these objects are located between the white dwarf and main sequence loci (Rebassa-Mansergas et al 2021).…”
Section: Search Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…This precision is, therefore, at or below the aim of 5 per cent precision which is necessary to discern systems with interesting subtypes of either component. Comparing these percentage uncertainties with the two other methods of characterisation mentioned -spectral decomposition (Rebassa-Mansergas et al 2012) and VOSA SED fitting (Rebassa-Mansergas et al 2021) -demonstrates that using the eclipse gives similar or better precision. For the WD mass, the median percentage uncertainty of the SDSS sample (Rebassa-Mansergas et al 3.…”
Section: Discussionmentioning
confidence: 84%
“…Common-envelope evolution, in particular, also produces a significant population of close, but detached white-dwarf/main-sequence (WDMS) binaries. Rebassa-Mansergas et al (2021) recently estimated a WDMS space density of 3.7 × 10 −4 pc −3 , implying the presence of 1500 such systems within a distance of 100 pc. Approximately a quarter of WDMS are close enough that they must be post-commonenvelope binaries (PCEBs), and 10% of these PCEBs exhibit eclipses (Rebassa-Mansergas et al 2016;Parsons et al 2013Parsons et al , 2015.…”
Section: Introductionmentioning
confidence: 99%